XMM-Newton Conclusively Identifies an Active Galactic Nucleus in a Green Pea Galaxy - Boorman, Peter G.; Svoboda, Jiří; Stern, Daniel; Lehmer, Bret D.; Borkar, Abhijeet; Brightman, Murray; Earnshaw, Hannah P.; Harrison, Fiona A.; Kouroumpatzakis, Konstantinos; Adamcová, Barbora; Assef, Roberto J.; Ehle, Matthias; et al. (The Astrophysical journal, 2025)
Green Pea galaxies are a class of compact, low-mass, low-metallicity star-forming galaxies in the relatively local Universe. They are believed to be analogs of high-redshift galaxies that reionized the Universe, and, indeed, the James Webb Space Telescope (JWST) is now uncovering such populations at record redshifts. Intriguingly, JWST finds evidence suggestive of active galactic nuclei (AGN) in many of these distant galaxies, including the elusive Little Red Dots, which broadly lack any detectable X-ray counterparts. Intuitively, one would expect to detect an AGN in their low-redshift analogs with X-rays, yet no study to date has conclusively identified an X-ray AGN within a Green Pea galaxy. Here we present the deepest X-ray campaign of a Green Pea galaxy performed to date, obtained with the goal of discerning the presence of a (potentially low-luminosity) AGN. The target—SDSS J082247.66+224144.0 (hereafter J0822+2241)—was previously found to display a comparable X-ray spectral shape to more local AGN (Γ ∼ 2) and a high luminosity ( L 2−10 keV ∼ 10 42 erg s −1 ). We show that over 6.2 yr (rest frame) the 2–10 keV luminosity of J0822+2241 is constant, whereas the soft 0.5–2 keV flux has decreased significantly by ∼60%. We discuss possible scenarios to explain the X-ray properties of J0822+2241, finding transient low column density obscuration surrounding an AGN to be the only plausible scenario. J0822+2241 thus provides further evidence that low-luminosity AGN activity could have contributed to the epoch of reionization and that local analogs are useful to derive a complete multiwavelength picture of black hole growth in high-redshift, low-luminosity AGNs.